Adenoid cystic carcinoma of the head and neck – An update. Issue 7 (July 2015) - Coca-Pelaz, Andrés; Rodrigo, Juan P.; Bradley, Patrick J.; Vander Poorten, Vincent; Triantafyllou, Asterios; Hunt, Jennifer L.; Strojan, Primož; Rinaldo, Alessandra; Haigentz, Missak; Takes, Robert P.; Mondin, Vanni; Teymoortash, Afshin; et al.
Highlights Adenoid cystic carcinoma is an uncommon salivary gland tumor. Updated current state of the art on head and neck adenoid cystic carcinoma. Emphasis on pathobiological advances on head and neck adenoid cystic carcinoma.